SERUM LEVEL OF EOSINOPHILIC CATIONIC PROTEIN IN RELATION TO EOSINOPHILIA AND TO EXHALED NITRIC OXIDE VALUE IN CHILDREN WITH ATOPIC ASTHMA AND AEROALLERGENS SENSITIZATION - Ana-Maria Moiceanu Sovărel; Eugenia Buzoianu; Mariana Moiceanu; Doina Anca Plesca (Amaltea Medical Publishing House, 2018)
Aim. To assess the correlation between the serum level of eosinophilic cationic protein (S-ECP) and the occurrence of eosinophilia, respectively the exhaled nitric oxide value (FeNO), in children with atopic asthma and aeroallergens sensitization. Material and method. A prospective study including 63 children with atopic asthma and aeroallergens sensitization aged 5-18 years old, conducted in Pediatric Department of Children Clinical Hospital "Dr. Victor Gomoiu", between April 2016 and July 2017. The S-ECP level, occurrence of eosinophilia and FeNO value were initially determined. Thereafter the statistically significance of the correlation between S-ECP and the occurrence of eosinophilia, respectively FeNO value, was assessed. Results. 22 patients had normal S-ECP level; among them only 8 had eosinophilia. 41 patients had increased S-ECP level; among them 28 had eosinophilia. Using the statistical function Pearson Chi-Square Test to assess the significance of the correlation between increased S-ECP level and eosinophilia we have obtained a p value = 0.0146 (statistically significant). 15 of those 22 patients with normal S-ECP level had at the same time a normal FeNO level; the other 7 patients had increased FeNO level. 17 of those 41 patients with increased S-ECP value had normal FeNO level; the other 24 patients had increased FeNO level. Using the statistical function Pearson Chi-Square Test to assess the significance of the correlation between S-ECP level and FeNO value we have obtained a p value = 0.0432 (statistically significant). Conclusion. Increased S-ECP level is correlated with the occurrence of eosinophilia and also with the increased FeNO value in atopic children with aeroallergens sensitization.